اثر استخدام معلومات التكاليف البيئية على الحسابات الاقتصادية (القومية) ودورها في تعزيز عملية التنمية المستدامة - د. صالح ابراهيم الشعباني (PROSPECTIVE RESEARCHES, 2023)
In the past, the national or economical accounts neglected the role of environment; which made, the economical account in most of the countries particularly the Arab countries, suffer from problem .Neglecting the environmental defects, the necessary costs to remove the effects of the previous pollution, putting an end to the present pollution and doing repairs of the environment. Makes the national product as an economic sign of inaccuracy .Moreover, the information provided by these accounts is of less use and not suitable to express the economical development. In addition, the developmental planning, policies, and programs which depend on this information is not trustworthy because it is not clear. In order to secure the existence of sustainable development, it is necessary to take into consideration the environmental costs in order that the economical signs (the national product and income) are nearer to reality and trustworthy to evaluate the development.